Locally invasive pulmonary inflammatory myofibroblastic tumors in children - Goel, Prabudh (Medknow Publications & Media Pvt Ltd, 2012)
Two uncommon cases of locally invasive pulmonary inflammatory myofibroblastic tumor are reported. Diagnosis was established by a prior thoracotomy and incisional biopsy. Complete excision was curative and both children remain asymptomatic at last follow up.